A construção da cidadania nos parâmetros curriculares nacionais para o ensino médio (PCNEM) - Silva, Nelson Peres da (2011)
This research analyzed critically and reflexively the new curricular proposal for Secondary Education, based on Brazilian Curricular Parameters, that was interpreted as public social policy for basic education in the 1990s. This current research utilized a theoretical method in an attempt to understand the citizenship concept since its origin in the Greek society and its journey in the humanity history; the education development in the Brazilian society since the Brazilian’s Independence; the basic education in the current days and the new curriculum proposal for Secondary Education by the Brazilian Curricular Parameters. The bibliography research results showed that the citizenship concept had mutations during the humanity history, it showed also its influences for an equality society development, and the Brazilian education arrangement based on ruling social groups interests. It has been showed that the Brazilian education has achieved significant advances in the last few decades, mainly with the National Constitution (1988), which has ensured the Secondary Education rights to all the Brazilian students, at least in constitutional terms. The analysis of the following items - Education Basis and Aims Act National Education, Curricular Basis for Secondary Education and Brazilian Curricular Parameters - has showed that the Secondary Education basis does not teach the citizenship concept, but its intend to training the students for the requirements of the capitalist market. The high rates of dropout and student low income contributed to turn the Secondary Education into social exclusion factor, and those factors should affect mainly poor social groups